Penilaian Penerapan Protokol Kesehatan COVID-19 dalam Situasi Pandemi di PT. Bank XYZ Tbk, Medan, Indonesia - Syahlan, Nabila; J. EL-Matury, Herlina (Jurnal Kesehatan Komunitas, 2024)
Background: Large-scale social Restrictions were implemented in the workplace during the COVID-19 pandemic from March 2020 to February 2022. The government has imposed restrictions on the number of workers in the workplace by implementing COVID-19 protocols at the workplace and work-from-home. This research aims to analyze the implementation of the COVID-19 protocol at PT. Bank XYZ Medan office. Methods: Observational descriptive research provides a clear picture by observing the conditions that occur directly to see how the COVID-19 protocol is implemented at PT.Bank XYZ Medan office. Quantitative methods are used. The instruments are the provision of Health Protocols from the Indonesian Minister of Health Decree No. 328 of 2020 regarding Guidelines for Preventing Control of COVID-19 in Office and Industrial Workplaces to Support Business Continuity in Pandemic Situations. Results: The implementation of the COVID-19 health protocol in the PT. Bank XYZ Medan office has a "Very Good" level of achievement. Companies can maintain the implementation of existing COVID-19 protocols during the pandemic to prevent the spread of the COVID-19 virus in the company. Conclusion: PT. Bank XYZ is expected to maintain the implementation of the COVID-19 protocol if the pandemic has not been declared over by the government of the Republic of Indonesia, and in the future improvements can be made to prevent the transmission of other diseases. Employees must continue to follow the regulations set by the company.